Reshaping Accountability In Village Fund Management: A Reflective Analysis From 2019 To 2023 - Petrus, Nicolaus; Florentin Werang, Maria Lusiana (Sociology Department, Brawijaya University, 2026)
Village fund management in Indonesia is still an unresolved issue, proportionally from the beginning of the reform to post-reform; interestingly, this problem is still seen in the analysis from 2019 to 2023, which suggests that accountability practices have not been entirely managed. Although this urgency has a dream in grassroots development, some barriers weaken its effectiveness. Then, our study adopted a quantitative descriptive methodology based on secondary data from the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia. The analysis revealed these barriers were limited administrative capacity, regulatory rigidity, ineffective monitoring systems, political interference, and inadequate community participation. Our findings demonstrate that despite the progress made, inconsistencies in accountability practices persist, so we advocate that central-local governments emphasize (e.g., capacity building, regulatory flexibility, technology-based monitoring, policy synchronization, and enlarged community participation). Finally, this study concludes that consistency of accountability in village fund management needs to be concretized proportionally, with several empirical recommendations suggested for consideration in village fund management, especially for formulating an effective practice on adaptive, inclusive, and innovative rural development.